2020
DOI: 10.1136/annrheumdis-2020-eular.3881
|View full text |Cite
|
Sign up to set email alerts
|

Op0164 bliss-Ln: A Randomised, Double-Blind, Placebo-Controlled Phase 3 Trial of Intravenous Belimumab in Patients With Active Lupus Nephritis

Abstract: Background:Lupus nephritis (LN), a serious manifestation of systemic lupus erythematosus (SLE), affects nearly 70% of patients (pts) in high-risk groups. To preserve renal function, LN requires fast and effective treatment. Despite medical advances, progression rates at 15 years to end-stage renal disease (ESRD) remain >40% for pts with diffuse proliferative LN. Belimumab (BEL), approved in pts aged ≥5 years with active SLE, improved renal parameters in pts with baseline renal involvement in apost hocanalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(2) Maintenance phase: which follows the induction phase and involves the continuation of immunosuppressive management. This phase aims at attaining a complete renal response and minimizing or preventing renal flares [46,47]. Sequential immunosuppressive treatments, such as cyclophosphamide followed by azathioprine, or monotherapy, such as MMF, can be used in both the induction and maintenance stages.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Maintenance phase: which follows the induction phase and involves the continuation of immunosuppressive management. This phase aims at attaining a complete renal response and minimizing or preventing renal flares [46,47]. Sequential immunosuppressive treatments, such as cyclophosphamide followed by azathioprine, or monotherapy, such as MMF, can be used in both the induction and maintenance stages.…”
Section: Discussionmentioning
confidence: 99%
“…Post marketing studies of Belimumab as well as registry data will provide further insights into real-life utility and its long-term safety profile. Abstract publication of BLISS-LN, a phase III trial of belimumab in patients with active LN demonstrated an 11% increased renal response rate when administering belimumab in addition to standard therapy compared to standard therapy alone (142). We await further studies of anti-BLyS treatment in African-American patients (143) and how other factors such as background therapy affect its outcomes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A recent phase III RCT (BLISS-LN) showed promise of belimumab in LN. [ 12 ] A total of 446 patients with biopsy-proven LN were randomized to receive either IV belimumab (10 mg/kg) or PBO in addition to SOC for induction therapy (74% mycophenolate mofetil (MMF); 26% cyclophosphamide (CYC)/azathioprine (AZA)). At Week 104, the primary outcome renal response (urine protein-to-creatinine ratio (uP/Cr) ≤0.7; estimated glomerular filtration rate (eGFR) ≤20% below pre-flare value or ≥60 mL/min/1.73 m 2 ; and no treatment failure) rate was significantly higher in the belimumab group compared with the than PBO group (43.0% vs. 32.3%; P = 0.03).…”
Section: Biological Therapies For Slementioning
confidence: 99%